Analysis the Effectiveness of Health Information Systems for Vaccine Intervention COVID-19 at Glenu Health Center Ermera Year 2023 - Guterres Magno, Nuno Pedro; Pereira Moniz, Elias; Faria Marçal, Suzi Bernardina; da Conceição Oliveira, Me. Lourença (Jurnal KESANS : Kesehatan dan Sains, 2025)
Introduction: Health Information Systems (HIS) play a vital role in enhancing healthcare delivery and decision-making processes. Effective implementation of the COVID-19 vaccination program is essential to control the pandemic globally. However, data from the Ministry of Health of Timor Leste reveals suboptimal vaccination coverage in Municipio Ermera, with only 78.9% receiving the first dose, 66.2% the second, and just 18.7% the third dose. These figures indicate a need for more efficient data management and health service delivery. Objective: This study aims to assess the effectiveness of the Health Information System in supporting COVID-19 vaccination efforts at the Glenu Ermera Health Center in 2023. Method: Using a quantitative cross-sectional design, data were collected from 59 healthcare workers. Analysis was performed using the Chi-Square test in SPSS version 21. Result and Discussion: Results showed that only 5.1% of respondents rated the HIS as effective, while 74.6% deemed it less effective. The chi-square analysis yielded a p-value of 0.013 (<0.05), indicating a significant relationship between HIS effectiveness and vaccination outcomes. Conclusion: In conclusion, enhancing HIS effectiveness at the Gleno Ermera Health Center requires comprehensive facility improvements, better regulations, and the development of skilled human resources.